Environmental signals rather than layered ontogeny imprint the function of type 2 conventional dendritic cells in young and adult mice - Papaioannou, Nikos E.; Salei, Natallia; Rambichler, Stephan; Ravi, Kaushikk; Popovic, Jelena; Küntzel, Vanessa; Lehmann, Christian; Fiancette, Remi; Salvermoser, Johanna; Gajdasik, Dominika W.; Mettler, Ramona; Messerer, Denise; et al. (Nature Communications, 2021)
Conventional dendritic cells (cDC) are key activators of naive T cells, and can be targeted in adults to induce adaptive immunity, but in early life are considered under-developed or functionally immature. Here we show that, in early life, when the immune system develops, cDC2 exhibit a dual hematopoietic origin and, like other myeloid and lymphoid cells, develop in waves. Developmentally distinct cDC2 in early life, despite being distinguishable by fate mapping, are transcriptionally and functionally similar. cDC2 in early and adult life, however, are exposed to distinct cytokine environments that shape their transcriptional profile and alter their ability to sense pathogens, secrete cytokines and polarize T cells. We further show that cDC2 in early life, despite being distinct from cDC2 in adult life, are functionally competent and can induce T cell responses. Our results thus highlight the potential of harnessing cDC2 for boosting immunity in early life.
CRIS-Team Scopus Importer:2021-01-29